Integrated Pest Management Efforts for Eco-friendly Agricultural Production in Nepal: A Perspective - GC, Yubak D. (Journal of the Plant Protection Society, 2018)
World-wide, Integrated Pest Management (IPM) has been considered one of the eco-friendly and powerful tools to manage crop pests. In Nepal, it has been adopted for more than two decades with its highest success in various crops. As dissemination and up-scaling tools to this approach, Farmers Field School (FFS) is being launched in numerous farming communities. The basic notion of initiation of this program was to mitigate and combat the negative consequence created by chemical pesticides while controlling insect pests in crops. In Nepal, it started in 1997 through a FAO Technical Cooperation Project (TCP). This article summarizes IPM activities ever since TCP to Second Phase of IPM Program (2008-2013) launched by the Government of Nepal with the support of Norwegian government. Until, 2012/013, altogether 3772 FFSs were conducted by PPD and FAO initiatives and 99751 farmers graduated in IPM Program, while 1175 farmers trained as IPM FFS Facilitators. More than 5000 farmers groups benefited from yearlong IPM FFS. Medium level agricultural technicians, government Officers from different disciplines and 25 participants from Council for Vocational Education and Training Centre (CTEVT) were trained as IPM Master Facilitators. IPM policy and participatory system of IPM product certification system were drafted however; they could not be finalized during the project period. Support for Master Degree studies and Bachelor degree mini-thesis were provided to students of various Agriculture Education Institution. Curricula developed for yearlong IPM FFS in different crops were adopted by CTEVT and other Institute in their academic programs. In the the later phase of project, emphasis was towards the institutionalization of the outcomes into regular program of the Government with a modified approach of bio pesticide production, plant clinics and networking. The program ignited and stressed largely on the socio-technical empowerment to the farmers and technicians. Initiation on the marketing of IPM products was also one of the outputs. This should be linked with increasing use of bio pesticides to the healthy food production so that environmentally damaging chemical pesticides may be reduced from the country.